HUBUNGAN TINGKAT PENGETAHUAN NYERI HAID DENGAN KESIAPAN REMAJA PUTRI MENGHADAPI MENARCHE PADA SISWI KELAS VII dan VIII DI SMP SEMINARI SAUMLAKI. - Fauziah, Arvicha; Kasmiati, Kasmiati; Jambormias, Jacob L. (SINERGI : Jurnal Riset Ilmiah, 2024)
Menarche's first menstruation requires careful planning and information assistance. Knowledge about menstrual pain will make young women ready to face menarche. The research aimed to determine the relationship between the level of pain knowledge and the readiness of young women to face menarche in class VII, and VIII students at Saumlaki Seminary Middle School. The research used a cross-sectional design with purposive sampling totaling 30 respondents. Questionnaires were used to collect data on knowledge of menstrual pain, readiness to face menstruation, and the Chi-Square statistical test for data analysis. The results of the research were that there was a relationship between the level of knowledge of menstrual pain and the readiness of young women to face menarche in class VII, and VIII students at Saumlaki Seminary Middle School (P-value = 0.001). The contingency coefficient value of -0.554 is interpreted as sufficient correlation strength. The conclusion is that the lower the level of knowledge about menstrual pain, the higher the adolescent's unpreparedness for facing menarche. The hope is that schools can increase understanding of menstrual